2017
DOI: 10.1186/s41100-017-0119-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the phosphate-binding effects of sucroferric oxyhydroxide, ferric citrate, and lanthanum carbonate

Abstract: Background: Iron-based phosphate binders are widely used in hemodialysis, to avoid the increased mortality associated with high serum phosphate in dialysis patients. However, comparative studies on the effects of phosphate binders are currently limited. In the present study, a comparative analysis of ferric citrate (FC), sucroferric oxyhydroxide (SF), and lanthanum carbonate (LC) was performed to assess their primary phosphate-binding and secondary iron uptake capacities. Methods: Patients on maintenance hemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Several studies have compared the phosphate-binding capacity of phosphate binders to date [1214]. Furthermore, Cannata-Andía et al have reported that the combined therapies with calcium-containing phosphate binders, sevelamer and lanthanum carbonate showed a beneficial association with survival in clinical practice [15]; however, there have been few detailed comparisons of phosphate-binding capacity in the combined therapies including new phosphate binders such as sucroferric oxyhydroxide.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have compared the phosphate-binding capacity of phosphate binders to date [1214]. Furthermore, Cannata-Andía et al have reported that the combined therapies with calcium-containing phosphate binders, sevelamer and lanthanum carbonate showed a beneficial association with survival in clinical practice [15]; however, there have been few detailed comparisons of phosphate-binding capacity in the combined therapies including new phosphate binders such as sucroferric oxyhydroxide.…”
Section: Introductionmentioning
confidence: 99%